Ответ:
[tex]\frac{6}{x^{2}-9}+\frac{x}{x+3}+\frac{2x}{9-x^{2}}= \frac{6}{x^{2}-9}+\frac{x(x-3)}{(x+3)(x-3)}-\frac{2x}{x^{2}-9}=\frac{6-2x+x^{2} -3x}{x^{2}-9} =\frac{x^{2} -5x+6}{x^{2}-9}=\frac{(x-3)(x-2)}{(x-3)(x+3)} =\frac{x-2}{x+3}[/tex]
x≠±3
Объяснение:
[tex]\frac{6}{x^2-9} +\frac{x}{x+3} -\frac{2x}{x^2-9}=\frac{6+x^2-3x-2x}{x^2-9} =\frac{x^2-5x+6}{x^2-9} =\frac{(x-2)(x-3)}{(x-3)(x+3)} =\frac{x-2}{x+3}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]\frac{6}{x^{2}-9}+\frac{x}{x+3}+\frac{2x}{9-x^{2}}= \frac{6}{x^{2}-9}+\frac{x(x-3)}{(x+3)(x-3)}-\frac{2x}{x^{2}-9}=\frac{6-2x+x^{2} -3x}{x^{2}-9} =\frac{x^{2} -5x+6}{x^{2}-9}=\frac{(x-3)(x-2)}{(x-3)(x+3)} =\frac{x-2}{x+3}[/tex]
x≠±3
Объяснение:
Ответ:
Объяснение:
[tex]\frac{6}{x^2-9} +\frac{x}{x+3} -\frac{2x}{x^2-9}=\frac{6+x^2-3x-2x}{x^2-9} =\frac{x^2-5x+6}{x^2-9} =\frac{(x-2)(x-3)}{(x-3)(x+3)} =\frac{x-2}{x+3}[/tex]